Sustainability Accounting in Developing Countries: Trends and Patterns in ESG Research (2015–2025) - Abid Ramadhan; Putri Dewintari; Antong; Halim Usman (IECON: International Economics and Business Conference, 2025)
This study aims to identify and analyze the development and trends in sustainability accounting research, particularly in the context of Environmental, Social, and Governance (ESG) issues within developing countries during the period from 2015 to 2025. By applying a bibliometric approach, this research utilizes secondary data sourced from reputable databases and processed using VOSviewer software to map the landscape of academic publications. The analysis includes publication volume, co-authorship networks, country collaborations, and keyword co-occurrence. The results indicate a significant increase in ESG-related studies, with China emerging as the leading contributor, followed by India and South Africa. Key research themes that have frequently appeared include ESG disclosures, corporate performance, climate change, renewable energy, and gender diversity in governance. These findings highlight both the progress and the existing gaps in ESG accounting research across developing nations. The study offers valuable insights for researchers, educators, and policymakers to better understand the dynamics of ESG integration in accounting practices and to guide future research directions in the field of sustainability accounting.